Multimedia-Based Learning Media Development to Improve Early Childhood Expressive Language Ability - Entep Hamdillah Ghofur; Sri Nurhayati (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
Currently, rapid technological development has led to children growing up as a more intelligent generation with the use of multimedia. However, on the other hand, it has not yet been able to provide a positive effect on educators and young children. The purpose of this study is to develop multimedia-based learning media and to produce valid, practical, and effective learning media products. The type of research conducted is research and development (RD). Data collection techniques used in this study are interviews and questionnaires. The development procedure refers to the ADDIE model. Based on the results of the validity test by 2 experts was categorized as valid, the practicality test by 2 educators was categorized as very practical, technical and economical, while the effectiveness test was conducted by 21 children aged 5-6 years with an effective category. The conclusion obtained is that multimedia-based learning media developed have been proven effective in improving the expressive language abilities of early childhood aged 5-6 years. The implication of this research is the need to produce multimedia-based learning media widely as an alternative form for teachers in using learning media to facilitate the delivery of material that can improve the expressive language abilities of early childhood aged 5-6 years.